RETRACTED: Opportunities to increase livestock production efficiency by developing agricultural services in Uzbekistan - Khurramov Azizbek; Tulakov Ulugbek; Soliyev Abdumalik; Djalilova Malika; Khurramova Madina; Ortikov Shavkat; Shaymardanov Abror (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001